Dampak globalisasi terhadap perilaku sosial identitas budaya lokal masyarakat Sade - Munaiah, Munaiah; Sri Rejeki; Zedi Muttaqien (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2024)
This study aims to examine the impact of globalization on the social behavior and local cultural identity of the Sade community, focusing on the changes that occurred before and after the transformation of Sade hamlet into a tourist destination. The research method used was qualitative using interviews as an instrument to obtain the views of various informants, including traditional leaders, master teachers, and the general public, regarding their perceptions of the impact of globalization. The results showed significant changes in several aspects, including consumption patterns, social values and norms, and the cultural identity of the Sade community. Globalization has affected people's consumption patterns, with an increasing preference for global products over traditional local products. In addition, there has been a shift in social values and norms, with individualistic values from global culture beginning to influence the social structure that was previously dominated by values of collectivity and solidarity in the Sade community. Changes in cultural identity also occur where interaction with global culture creates new dynamics in the understanding and experience of the Sade community's cultural identity. Awareness of the importance of cultural preservation and traditional values becomes crucial in maintaining the authenticity of local identity amidst the continuous flow of globalization.